Jesus Centered Leadership and Business Applications: An Alternative Approach. (4th December 2017) - Peters, Richard; Ricks, Joe M.; Doval, Christopher
Abstract: In this article we evaluate Jesus Centered Leadership (JCL), a new concept that has emerged in the realm of spirituality and business management. JCL questions the "Christianity" of Christian business leadership, and proposes principles for ethical leadership that provide a truer representation of the teachings and traits of Jesus. We consider these principles and contribute principles of our own, thereby providing an alternative approach to JCL that remains consistent with the JCL message of morality but addresses issues that offer greater opportunities for adoption within existing business and institutional models.